Transcranial direct current stimulation as treatment for major depression in a home treatment setting (HomeDC trial): study protocol and methodology of a double-blind, placebo-controlled pilot study - Ulrike Kumpf; Harry Ezim; Matthias Stadler; Gerrit Burkhardt; Ulrich Palm; Esther Dechantsreiter; Frank Padberg (Pilot and Feasibility Studies, 2023)
Abstract Introduction Transcranial direct current stimulation (tDCS) of prefrontal cortex regions has been reported to exert therapeutic effects in patients with major depressive disorder (MDD). Due to its beneficial safety profile, its easy mode of application, and its cost-effectiveness, tDCS has recently been proposed for treatment at home. This would offer new chances for regionally widespread and long-term application. However, tDCS at home must meet the new methodological challenges of handling and adherence. At the same time, data from randomized controlled trials (RCT) investigating this mode of application are still lacking. In this pilot RCT, we therefore investigate the feasibility, safety, and effectiveness of a new antidepressant tDCS application set-up. Methods and analysis The HomeDC trial will be conducted as a double-blind, placebo-controlled, parallel-group design trial. Thirty-two study participants with MDD will be randomly assigned to active or sham tDCS groups. Participants will self-administer prefrontal tDCS for 6 weeks. Active tDCS will be conducted with anode over F3, cathode over F4, for 5 sessions/week, with a duration of 30 min/day, and 2 mA stimulation intensity. Sham tDCS, conversely, follows an identical protocol in regard to electrode montage and timing, but with no electric stimulation between the ramp-in and ramp-out periods. Both conditions will be administered either as a monotherapy or an adjunctive treatment to a stable dose of antidepressant medication. Adjunctive magnetic resonance imaging (MRI) and electric field (E-field) modelling will be conducted at baseline. Primary outcome is feasibility based on successfully completed stimulations and drop-out rates. The intervention is considered feasible when 20 out of 30 sessions have been fully conducted by at least 75% of the participants. Effectiveness and safety will be assessed as secondary outcomes. Discussion In the HomeDC trial, the technical requirements for a placebo-controlled tDCS study in a home-based treatment setting have been established. The trial addresses the crucial points of the home-based tDCS treatment approach: uniform electrode positioning, frequent monitoring of stimulation parameters, adherence, and ensuring an appropriate home treatment environment. This study will further identify constraints and drawbacks of this novel mode of treatment. Trial registration www.ClinicalTrials.gov . Trial registration number: NCT05172505. Registration date: 12/13/2021.